Etcetera: scale and indifference. Issue 7 (9th August 2019) - Aquilina, Aaron
ABSTRACT: Starting from a NASA infographic which inadvertently highlights how we often understand cosmic objects solely in comparison to Earth and its occupants, this essay foregrounds the idea of human insignificance as one often associated with thoughts about the scale of the universe. Indeed, when looking up, scale seems to go on forever: planet, solar system, galaxy, and on eternally, etcetera. In order to examine this issue, the present argument takes the seemingly oblique route of looking at poetry, specifically Don Paterson's 'Scale of Intensity', so as to expound three issues: (i) whether 'scale' and its hierarchies are best understood epistemologically or ontologically; (ii) how certain literary and philosophical works (particularly in terms of nihilism and eliminative ontologies) address the conjoint problems of scale and insignificance, this mostly through a rumination of the philosophical term ' sub specie aeternitatis '; (iii) and, finally, whether feelings of insignificance necessarily entail ones of indifference. In its concluding movement, this essay looks to Sextus Empiricus's particular reading of indifference, ultimately turning also to Albert Camus's 'The Myth of Sisyphus', which is here understood as offering a rejoinder to the seemingly incommensurable arguments on whether the human race ultimately matters, or not.